PELATIHAN PENERAPAN AKUNTANSI BAGI USAHA BIDAN PRAKTEK MANDIRI DI KECAMATAN SUKOMORO KABUPATEN NGANJUK JAWA TIMUR (Fakultas Ekonomi Universitas Islam Kadiri (UNISKA) Kediri, 2024)
Abstract The problems faced by partners (independent midwives) include that the finances of the midwife's practice business are still one with personal or family finances, some midwives may have implemented accounting records, but they are still not in accordance with accounting principles, or their application is still not consistent between periods, or even not do the accounting records at all. The purpose of this activity is to provide information about the implementation of accounting application training activities for midwives practicing independently in the Sukomoro District, Nganjuk Regency which includes activity material, location, time, and the effectiveness of the results of the activity implementation. The results of this training have made Midwives have simple accounting knowledge and skills that can be applied in their business, preparing periodic financial reports, evaluating financial performance, calculating payable taxes, and other business decisions.. Keywords: application of accounting, independent practice midwives Abstrak Masalah yang dihadapi mitra (bidan mandiri) antara lain keuangan usaha praktek bidan masih menjadi satu dengan keuangan pribadi atau keluarga, beberapa bidan mungkin sudah menerapkan pencatatan akuntansi, namun masih belum sesuai dengan kaidah akuntansi, atau masih belum konsisten penerapannya antar periode, atau bahkan tidak melakukan pencatatan akuntansi sama sekali. Tujuan kegiatan ini memberikan infomasi tentang pelaksanaan kegiatan pelatihan penerapan akuntansi bagi usaha bidan praktek mandiri di wilayah Kecamatan Sukomoro Kabupaten Nganjuk yang mencakup materi kegiatan, lokasi, waktu, dan efektivitas hasil pelaksanaan kegiatan. Hasil pelatihan ini membuat Bidan memiliki pengetahuan dan ketrampilan akuntansi sederhana yang dapat diterapkan dalam usahanya, menyusun laporan keuangan periodik, mengevaluasi kinerja keuangan, menghitung pajak terutang, dan keputusan bisnis lainnya. Kata Kunci: penerapan akuntansi, bidan praktek mandiri